2017
DOI: 10.1017/s0030605316001514
|View full text |Cite
|
Sign up to set email alerts
|

From Marxan to management: ocean zoning with stakeholders for Tun Mustapha Park in Sabah, Malaysia

Abstract: Tun Mustapha Park, in Sabah, Malaysia, was gazetted in May 2016 and is the first multiple-use park in Malaysia where conservation, sustainable resource use and development co-occur within one management framework. We applied a systematic conservation planning tool, Marxan with Zones, and stakeholder consultation to design and revise the draft zoning plan. This process was facilitated by Sabah Parks, a government agency, and WWF-Malaysia, under the guidance of the Tun Mustapha Park steering committee and with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 54 publications
1
37
0
1
Order By: Relevance
“…Such displacement would substantially decrease opportunity costs and alleviate conservation conflicts with all resource users, but especially with one of the most widespread and important extractive activities worldwide: fishing (Kroodsma et al, ). The incorporation of socio‐economic information would thus help to achieve a balance between development and conservation goals, as evidenced by studies in other countries with broad dependency on sea resources (Jumin et al, ; Li et al, ; Mazor et al, ). However, explicitly including the broad range of qualitative elements of the Aichi Target 11 (Rees, Foster, Langmead, Pittman, & Johnson, ) could create additional trade‐offs, not addressed here, among planning objectives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such displacement would substantially decrease opportunity costs and alleviate conservation conflicts with all resource users, but especially with one of the most widespread and important extractive activities worldwide: fishing (Kroodsma et al, ). The incorporation of socio‐economic information would thus help to achieve a balance between development and conservation goals, as evidenced by studies in other countries with broad dependency on sea resources (Jumin et al, ; Li et al, ; Mazor et al, ). However, explicitly including the broad range of qualitative elements of the Aichi Target 11 (Rees, Foster, Langmead, Pittman, & Johnson, ) could create additional trade‐offs, not addressed here, among planning objectives.…”
Section: Discussionmentioning
confidence: 99%
“…Such displacement would substantially decrease opportunity costs and alleviate conservation conflicts with all resource users, but especially with one of the most widespread and important extractive activities worldwide: fishing (Kroodsma et al, 2018). The incorporation of socio-economic information would thus help to achieve a balance between development and conservation goals, as evidenced by studies in other countries with broad dependency on sea resources (Jumin et al, 2017;Li et al, 2019;Mazor et al, 2014 In Brazil, as in many countries around the world (Klein et al, 2008;Mazor et al, 2014), large and small-scale fisheries are the major constraints for protecting high-priority areas. Given the growing geographical expansion of marine fisheries (Swartz, Sala, Tracey, Watson, & Pauly, 2010), the barriers imposed by the fishing sector to marine protection should increase in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors contributed to this situation. Malaysia and Timor Leste each had only one instance of systematic conservation planning at the time of our analysis (Edyvane et al 2012, Jumin et al 2018). In the Philippines, where there is upward of 1200 marine protected areas (Horigue et al 2012), only one conservation plan could be identified.…”
Section: Limitationsmentioning
confidence: 99%
“…Prioritization is often contained within a larger systematic conservation planning (SCP) process, which uses one or more operational models to design and translate prioritizations to on-the-ground conservation action (Groves & Game, 2015;Kukkala & Moilanen, 2013). Central among the recommendations made by these models and the supporting literature are the involvement of stakeholders in the development process, identification, and collaboration with end users early in the process and the delivery of final products in a user-useful format, such as by producing supporting documents (Jumin et al, 2017;Knight, Cowling, Boshoff, Wilson, & Pierce, 2011;Pierce et al, 2005;Theobald et al, 2000). These approaches help deliver conservation outcomes through improving stakeholder buy-in, increasing trust, and improving communication (Bottrill, Mills, Pressey, Game, & Groves, 2012;Knight et al, 2006;Pierce et al, 2005).…”
Section: Introductionmentioning
confidence: 99%